THE ROLE OF NO SYNTHESIS CORRECTION IN PREVENTION OF CARDIOVASCULAR HYPERTENSIVE REMODELING - V. I. Buvaltsev; S. Y. Mashina; D. A. Pokidyshev; B. V. Smirin; L. A. Bayda; V. Y. Malyshev; E. B. Manukina (Российский кардиологический журнал)
Comparative study of preventive effects of two beta-blocking drugs with different mode of action was performed on SHRSP and WKY rats. Morphological and functional parameters – blood pressure, endothelium-dependent vascular relaxation, plasma level of nitric oxide stable metabolites (nitrite/nitrate), cardiac hyperthrophy and vascular remodeling were monitored during chronic nebivolol and metoprolol injection in parallel groups of rats. Nebivolol, a cardioselective beta-blocker with ancillary nitric oxide modulating and vasodilating properties exhibited more significant and stable influence on the monitored parameters than metoprolol lacking the nitric oxide modulating activity and more effectively prevented cardiovascular remodeling in experimental hypertension.